Comparison of Smart City Program in Indonesia and China Study Case: Jakarta and Beijing - Tarissa, Devayana (Journal of Infrastructure Policy and Management (JIPM), 2023)
Smart City was created to shape a city to improve the quality of life by using urban information and technology to improve service efficiency and meet the needs of citizens, to create a safe, comfortable, controlled, and easy-to-access environment for its citizens and strengthen the city’s competitiveness in terms of the economy, social, and technology. This study discusses the smart city implementation in Indonesia with the 100 Smart Cities program and the smart city program in China. The study concept compares smart city programs in Jakarta and Beijing, which both cities have the same hard infrastructure conditions. It is hoped that this study can differentiate regarding the smart city approach in Indonesia and China. The method used in this paper is to conduct a literature study by comparing it with empirical conditions. The recommendation of this study is differences and similarities based on adjustment for the local conditions in Indonesia and China.